Protocol for investigating light/dark locomotion in larval stage zebrafish using a standardized behavioral assay - Courtney Hillman; James Kearn; Matthew O. Parker (STAR Protocols)
Summary: Zebrafish (Danio rerio) larvae offer a unique avenue for high-throughput in vivo investigation. The light/dark locomotor assay is widely used but lacks experimental consistency. Here, we present a protocol for a standardized light/dark assay by describing the steps for plating, acclimatizing larvae, performing the assay, and preparing drug exposure solutions. We also detail procedures for substance exposure and data analysis.For complete details on the use and execution of this protocol, please refer to Hillman et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.